Establishing the technical performance of the chain excavator with cutters working in conditions critical deep cutting of soils - Goponov, Alexey (Transfer of innovative technologies, 2021)
The calculated dependence for determination of technical productivity of the chain excavator with the cutters working in the conditions of critical depth cutting of soils is offered. An assessment is given for the practical implementation of the research results.